Knowledge, Attitude, and Practice of Patients toward Dental Implants in Need of Prosthodontic Rehabilitation - V Madhuri; Sindhu S Kumararama; Anupama Aradya; Brijesh Byrappa; Kamlesh Singh; Arti Dixit; Amit Kumar; Bhumika K Badiyani (Wolters Kluwer Medknow Publications, 2023)
Background: Our goal in conducting this study was to see how well-informed patients are about dental implants as a method of prosthodontic rehabilitation. Materials and Methods: "In this cross-sectional study, 500 new dental students were asked questions using a pre-made, self-administered questionnaire. A pilot study was carried out to verify the reliability of the survey instrument. Analysis of the data was performed in SPSS 16 (SPSS). We used the P 0.05 thresholds for the Student's T-test and the ANOVA to determine statistical significance." Results: In all, there were 500 people involved: 320 men and 180 women. The media and dentists were the two most common places to learn about implants, and as patients received more information, they became more informed consumers. Many people put off getting therapy because of how expensive it is. Conclusion: Only a small percentage of individuals had implants, and more than half knew nothing about them. This finding also highlighted the need of educating patients more thoroughly on this therapy option. As a result, the public has to be educated about oral health and implants in order to adopt a more favorable perspective.